PERFORMANCE IMPROVEMENT MODERATED BY ORGANIZATIONAL CULTURE - Rini Andriani; Kiki Farida Ferine (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
This study aims to analyze the influence of organizational culture, communication, and managerial support on employee performance, with communication and organizational culture serving as moderating variables. The research was conducted at the Treasury Division of PLN Head Office, involving a population of 270 employees, all of whom were selected as samples using a census technique. A quantitative approach was employed, and data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method via SmartPLS software. The results showed that organizational culture, communication, and managerial support have a positive and significant effect on employee performance. However, the moderating effects of communication and organizational culture on the relationship between the independent variables and performance were found to be insignificant. These findings highlight the importance of a strong organizational culture, effective communication, and solid managerial support in improving employee performance, particularly in complex organizational environments such as PLN. This research contributes theoretically to the field of human resource management and provides practical suggestions for organizational management in the electricity sector.